2017
DOI: 10.1002/2016ms000815
|View full text |Cite
|
Sign up to set email alerts
|

Framework for improvement by vertical enhancement: A simple approach to improve representation of low and high‐level clouds in large‐scale models

Abstract: Low and high clouds of shallow extent, especially stratocumulus and even more so for high‐level cirrus clouds that reside where vertical resolution is particularly coarse, are poorly represented in large‐scale models such as global climate models and weather forecasting models. This adversely affects, among others, estimation of cloud feedbacks for climate prediction and weather forecasts. Here we address vertical resolution as a reason for the failure of these models to adequately represent shallow clouds. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…The companion paper of Lee et al. (2021) addresses a potential solution, which involves the implementation of the Framework for Improvement by Vertical Enhancement (FIVE, Yamaguchi et al (2017)) to E3SM. The implementation of FIVE into E3SM will allow select physics processes to be run on a higher vertical resolution grid relative to the rest of model, which could provide a useful framework in obtaining similar results seen in this article but with a computation cost that is more digestible.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The companion paper of Lee et al. (2021) addresses a potential solution, which involves the implementation of the Framework for Improvement by Vertical Enhancement (FIVE, Yamaguchi et al (2017)) to E3SM. The implementation of FIVE into E3SM will allow select physics processes to be run on a higher vertical resolution grid relative to the rest of model, which could provide a useful framework in obtaining similar results seen in this article but with a computation cost that is more digestible.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, while Bogenschutz et al (2012) found that the Community Atmosphere Model (CAM) coupled with CLUBB produces an improved simulation of stratocumulus and cumulus-under-stratocumulus regimes, compared to the control version of CAM when the standard 30 layer configuration was used, it wasn't until the vertical resolution was increased by a factor of four when cloud and temperature profiles more resembled those of observations and LES. Yamaguchi et al (2017) found substantial improvements in the simulated stratocumulus layer for CRMs when physics processes (including CLUBB) were run at much higher vertical grid than dynamical processes.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the multiscale modeling framework (an embedded cloud resolving model within a GCM grid box) [48,104,111,117] provides a way forward. Vertical resolution is a persistent problem for shallow clouds, particularly stratocumulus, and new ideas have been proposed to locally apply an adaptive vertical mesh [85,159] …”
Section: The Scale Gap In Gcmsmentioning
confidence: 99%
“…To alleviate the computational expense of using a large number of vertical levels, new modeling techniques, such as the Framework for Improvement by Vertical Enhancement (FIVE;Yamaguchi et al 2017), may be incorporated in future efforts in which resolving strong vertical gradients is desired.…”
mentioning
confidence: 99%